African economic and financial data - United Nations Development Programme; World Bank. (New York, N.Y. : United Nations Development Programme ; Washington, D.C. : World Bank, 1989)
This is an information document intended to provide Africans and those interested in Africa a consistent and convenient set of data to monitor development programmes and aid flows in the region.
Includes bibliographical references
oif 31/01/2019
Ref.
Keywords: Economic indicators; Finance; Economic history; Social conditions; Africa